Electrogenerative Removal Of Cobalt Ions From Chloride Media Using A Batch Cell - Soh, Wen Min (2013)
Cobalt was recovered electrogeneratively by using a batch cell. In this system, a spontaneous chemical reaction occurred where cobalt is reduced at the cathode and zinc is oxidized to produce a free flow of electrical energy. The performances of reticulated vitreous carbon (RVC) and porous graphite (PG) as cathodes were evaluated based on the time and percentage of removal in an electrogenerative cell. RVC was able to recover 99.9% of cobalt in 120 min compared to 210 min for PG. The superiority of RVC cathode was expected as it obtained the highest reductive peak current density of 8.60 mA cm-2 compared to 6.42 mA cm-2 of PG in the electrodeposition of cobalt by means of cyclic voltammetry. The electrogenerative system also appeared to be less polarised with RVC as cathode. Besides that, a series of experiments were carried out to determine the best medium for the recovery of cobalt by means of an electrogenerative system. Use of the electrogenerative system with a chloride medium and RVC cathode had shown promising performance with the highest free energy of -389.8 kJ mol-1 compared to that with sulfate and nitrate media. Cyclic voltammetric data obtained with the three media also supported that chloride medium was the better medium which catalysed the cobalt deposition since it generated the highest reductive peak current densities at all concentrations of cobalt. The electrogenerative system with chloride medium was also the least polarised among the other mediums.